Violência física interpessoal: uma análise de série temporal e espacial dos casos de agressão familiar e comunitária para a região metropolitana de Campina Grande, Paraíba - Kevan Guilherme Nóbrega Barbosa (2018)
The present thesis analyzed from a temporal, spatial and epidemiological perspective the victims of interpersonal physical violence. Data were obtained consulting the medical-dental reports of the Nucleus of Medicine and Dentistry LegalNUMOL of Campina Grande. The census was conducted for cases of physical violence between 20082014. The temporal analysis described the rates per 100,000 population and used the correlogram (series association). Visual inspection of the series was based on the graphical elaboration through lowess method (locally weighted scatterplot smoothing) from the tri-cubic function. The inferential analyze was carried out through negative binomial regression. We used the meter Incidence Rate Ratio (IRR) to calculate the time effect; the sex of the victims and perpetrators effect, as well as the dummy interaction (cut time in the series). The epidemiological analysis used the binary and multiple logistic regression to verify significant associations among the variables (as reference comparison the familial violence). The spatial distribution was based on Kernel Density Estimation (KDE). Data from the Brazil IBGE-2010 Census was also used to characterize the location of the census tract which each victim resided. Between 20082014 occurred 3.321 cases familial violence and 4.634 cases of community violence. The annual rate of familial violence was 6.8/100,000 in 2008, increasing to 12.6 /100,000 in 2014 (an increase of 11.3% per year, p<0,001). The community violence registered a decrease of 18.8 /100,000 in 2008 to 9.6/100,000 in 2014 (decline of 11% per year, p<0,001). There was a significant increase in the familial violence cases over time involving female victims (p<0,001) and male perpetrators (p<0,001). In the community violence, the rates significant declined regardless the victims sex (p<0,001), and significant reduction for violence perpetrated by men (p=0,017). The analysis for dummy interaction (2012 as cut time), we observed that after 2012 the growth of female victims was even higher than the previous time in the familial violence (p=0,007) and a significant decrease of men perpetrators in the community violence (p<0,001) after 2012. The epidemiologic distribution showed the following association: woman victims; single; divorced; firearm use; mixed object use and men perpetrator. The spatial analysis evidenced seven hotspots for violence, with most victims resident on the East side of the city. Hotspots for physical violence were concentrated for victims living in areas coinciding with lower familial income by census tract. The data of the present thesis suggests an alarming fact for the situation of domestic violence against woman, due to a significant temporal increase of the cases. In addition, man has been predominantly responsible for the aggression in this type of violence. On the other hand, there was a decline in community violence and a drop for male aggressors, a positive factor. The spatial analysis made it clear that some areas of the urban zone under study have a considerable concentration of resident victims, as well as residing in the census tracts with low economic level (income). Keywords: Violence. Times series analysis. Domestic violence. Spatial analysis. Epidemiology. Wounds and injuries. Facial injuries.